An Administration Based on the Four Principles of Brahmaviharas of the Ecclesiastical School Administrators in Loei Province - ไวชมภู, พระทวีศักดิ์; แก้วอินทร์, ดุษฎีวัฒน์; จันปุ่ม, สุภชัย (Journal of Roi Et Rajabhat University, 2016)
The purposes of this research were to 1) study the administration based on the Four Principles of Brahmaviharadharas of Ecclesiastical schools’ administrators in Loei Province and 2) compare the application of the Four Principles in administration of Ecclesiastical schools’ administrators in Loei Province classified by gender , position, education qualification, and work experience of the sample. 169 personnel of ecclesiastical schools in Loei Province working during the academic year 2014 were selected as the sample of this study. The research instrument for collecting the data was a rating scale questionnaire. The data were analyzed using frequencies, percentages, means, and standard deviations. The research hypotheses were tested by t-test and F-test. Results of the study were as follows: 1. The opinions perceived by the personnel concerning the application of the Four Principles of Brahmaviharas in educational administration of the ecclesiastical school administrators in Loei Province in overall were rated at a high level. 2. The opinions concerning the application of the Four Principles of Brahmaviharas in educational administration of the ecclesiastical school administrators perceived by the personnel classified by gender, position, education qualification, and work experience both in overall and in each aspect were not different.